Plasma C‐Reactive Protein and Haptoglobin Concentrations in Critically Ill Neonatal Foals. (March 2015) - Zabrecky, K.A.; Slovis, N.M.; Constable, P.D.; Taylor, S.D.
Abstract : Background: Accurate diagnostic markers for sepsis in neonatal foals are needed. Plasma C‐reactive protein concentration (p[CRP]) and haptoglobin concentration (p[Hp]) are well‐established biomarkers of infection in humans, but studies are lacking in foals. Hypotheses: p[CRP]) and p[Hp] are increased in septic foals compared to sick nonseptic and healthy control foals, and are predictive of survival. Animals: Eighty critically ill foals (40 septic, 40 sick nonseptic) and 39 healthy control foals <1 week of age. Methods: Multicenter, prospective observational clinical study. Venous blood was collected at admission from septic and sick nonseptic foals and from clinically healthy foals at 24 h of age. A diagnosis of sepsis was made based on positive blood culture or a sepsis score >11, and p[CRP] and p[Hp] were measured by using ELISA tests. Data were analyzed by using the Mann‐Whitney U ‐test and forward stepwise multivariable linear regression. P < .05 was considered significant. Results: Plasma [CRP] was positively associated with age, serum globulin, adrenomedullin, and bilirubin concentrations, aspartate aminotransferase activity, glutamyl‐transferase activity, band neutrophil count, and rectal temperature, and was increased in foals with toxic neutrophils, enterocolitis, colic, rib fractures and septic arthritis. Surprisingly, p[Hp] was lower in septic foals than in sick nonseptic foals. Neither p[CRP] or p[Hp] was predictive of survival in critically ill foals. Conclusions and Clinical Importance: Plasma [CRP] increases with inflammation in neonatal foals but is not indicative of sepsis. Single time point, admission sampling of p[CRP] and p[Hp] do not appear to be useful biomarkers for sepsis in foals.